The Hydrogeological and Biological Characteristics of Psoriasis Treatment Center, Turkey - Mustafa Değirmenci; Bülent Ünver (Turkish Journal of Agriculture: Food Science and Technology)
More than 1000 thermal and mineral water springs with temperatures from 20°C to102°C occur in Turkey. Kangal Balikli Hot Spring is known as psoriasis treatment center is one of the most important among these springs. The main scope of this research was to determine geological, hydrogeological and biological properties and water chemistry of the psoriasis treatment center and the stream running alongside the thermal pools. The spring water is an isothermal-hypotonic and oligometalic mineral water, having average of electrical conductivity: 530 μS cm-1, temperature: 35°C, CO2 8.70 mg l-1, pH 7.30 and O2 4 mg l-1. Calcium, magnesium and bicarbonates are dominant. Neither the chemical figures nor the temperature (35±1°C) of the water shows seasonal change. There are two fish species, Garra rufa and Cyprinion macrostomus, that adapted living at 35°C water temperature. The mean fork length and body weight of the fish living in the psoriasis treatment center is significantly lower than those living at the stream. Some of the fish in the pools showed symptoms of illness such as exophthalmus, scale loose, skin ulceration, pale gills, and bloated appearance. Gut analysis revealed that both species have been feeding on algae, insect parts, fish scales, and debris. In most cases the guts of fish caught in the pools were either empty or had very little content in it. Zooplanktons had little species and were not recorded frequently.